A nanoindentation study of the deformation mode for nanostructured ductile/brittle multilayers: cracking versus shear banding. (3rd October 2019) - Feng, L.; Zhou, Q.; Jia, Q.; Shi, Y.D.; Wang, Y.; Zhao, X. H.
ABSTRACT: Nanostructured multilayer thin films (Ag/W, Cu/Ru, Cu/W), consisting of alternating ductility/brittle layers with wide ranges of modulation period ( Λ ) and modulation ratio ( η ), were prepared by magnetron sputtering. Under nanoindentation, cracking and/or shear banding behaviour was observed, which depended directly on the layer thickness of ductile and brittle layers respectively. By considering the distinct competition between crack initiation/propagation in brittle layers and the shielding/anti-shielding effect in ductile layers, the different deformation modes between these multilayers are discussed in terms of a micromechanical fracture criterion. The findings could be used in the design of nanostructured materials for superior toughness and deformation stability.